ANALISIS PENGARUH VARIABEL MAKRO TERHADAP KINERJA REKSADANA SYARIAH DI INDONESIA DAN MALAYSIA PERIODE 2011-2017 - Hairunnisa (Program Studi Perbankan Syariah, 2020)
This study aims to analyse the effect of inflation, currency exchange, economic growth and crude oil price on the performance of islamic mutual funds in Indonesia and Malaysia in 2011-2017. The purpose of this study is to analyse the difference between the performance of islamic mutual funds in Indonesia and Malaysia. All types of mutual funds in Indonesia and Malaysia are used in this study and tested using Ordinary Least Square (OLS) method. Simultaneously, inflation, currency exchange, economic growth and crude oil price have an effect on the performance of both Indonesia and Malaysia. Partially, it is found that inflation, currency exchange and crude oil price do not have any effect on islamic mutual funds in Indonesia and Malaysia. However, economic growth has only a significant effect on Indonesia???s mutual funds but not Malaysia.